Business Information Systems Workshops : BIS 2016 International Workshops, Leipzig, Germany, July 6-8, 2016, Revised Papers /: BIS 2016 International Workshops, Leipzig, Germany, July 6-8, 2016, Revised Papers. (2017) - Unknown
No abstract available